Randomised controlled trial of standard outpatient cardiac rehabilitation versus personalised cardiac rehabilitation for secondary prevention for all in need (SPAN) after type 1 myocardial infarction - David Brieger; Tom Briffa; Julie Redfern; Derek P Chew; John Atherton; Jamie Rankin; Charley Budgeon; Andrew Maiorana; Anne Cordingley; Stephen Nicholls; Graham Hillis; Teagan Robinson; et al. (BMJ Open, 2025)
Introduction Cardiac rehabilitation after type 1 myocardial infarction (type 1 MI) is an effective but underutilised method of preventing new cardiac events. This study aims to determine whether a programme of personalised cardiac rehabilitation achieves better completion rates compared with a routine outpatient rehabilitation model post-type 1 MI. A secondary aim is to determine any differences in rates of major adverse cardiovascular events at 12 months.Methods and analysis Secondary prevention for all in need (SPAN) is a prospective multisite single-blind comparative effectiveness randomised trial of personalised versus standard outpatient rehabilitation. Five hundred and thirty-two patients with a recent type 1 MI diagnosis will be randomised to either a personalised model of rehabilitation which includes flexibility in the components of rehabilitation and the time and location of contacts, or the standard outpatient model. Exclusion criteria include conditions associated with higher clinical risk to the participant, which introduce confounding to the study or interfere with a participant’s ability to comply.The primary study endpoint is the proportion of patients who complete the assigned rehabilitation model. Completion of rehabilitation is defined as participation in ≥80% of all scheduled sessions, in either treatment arm. Assuming a power of 90% and an overall type 1 error of 5%, we expect that 50% of those randomised to usual care will meet the primary endpoint compared with 65% of those on personalised rehabilitation. To detect this difference of 15%, we require a sample size of 478 participants (239 per arm). Accounting for a conservative attrition rate of 10%, the total sample size required is 532.Ethics and dissemination The trial received ethical approval from the Southern Adelaide Clinical Human Research Ethics Committee (ref. 2022/HRE00071) in September 2022, with an opt-out approach. The findings will be disseminated through peer-reviewed journals.Trial registration number ACTRN12622000316707.